Additive for positive electrodes of lithium secondary batteries, manufacturing method of the same, and lithium secondary batteries including the same

KR103022366B1Active Publication Date: 2026-09-18LG CHEM LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
KR1020220147036
Authority / Receiving Office
KR · KR
Patent Type
Patents
Current Assignee / Owner
Filing Date
2022-11-07
Publication Date
2026-09-18
Estimated Expiration
2042-11-07

Smart Images

  • Figure R1020220147036_ABST
    Figure R1020220147036_ABST
Patent Text Reader

Abstract

The present invention relates to a cathode additive for a lithium secondary battery, a method for manufacturing the same, and a lithium secondary battery including the same. According to the present invention, a cathode additive is provided that can improve the safety of a lithium secondary battery by having a stable crystalline phase while enabling an improvement in irreversible capacity.
Need to check novelty before this filing date? Find Prior Art

Description

Technology Field

[0001] The present invention relates to a positive electrode additive for a lithium secondary battery, a method for manufacturing the same, and a lithium secondary battery containing the same. Background Technology

[0003] As power consumption increases along with the multifunctionality of electronic devices, there are many attempts to increase the capacity of lithium-ion batteries and improve their charge and discharge efficiency.

[0004] For example, a technology has been proposed in which a cathode active material with 80% or more Ni is applied as a cathode material to the positive electrode of a lithium secondary battery, and a metal or metal-based negative electrode active material such as SiO, Si, or SiC is applied together with a carbon-based negative electrode active material such as natural graphite or artificial graphite to the negative electrode.

[0005] Metal and metal oxide-based cathode active materials enable the expression of higher capacity than carbon-based cathode active materials. However, because the volume change of metal and metal oxide-based cathode active materials during charging and discharging is much greater than that of graphite, it is difficult to increase the content of metal and metal oxide within the cathode to more than 15%. Furthermore, when metal and metal oxide are added to the cathode, irreversible reactions occur during the initial charging and discharging, resulting in greater lithium loss compared to the case where carbon-based cathode active materials are applied. Consequently, when metal and metal oxide-based cathode active materials are applied, the amount of lithium lost increases as the battery capacity increases, and the resulting decrease in initial capacity also becomes larger.

[0006] Accordingly, various methods have been studied to increase the capacity of lithium-ion batteries or reduce irreversible capacity. One of these is pre-lithiation, a concept that replenishes the lithium consumed in the formation of the SEI layer (solid electrolyte interphase layer) within the battery during the initial state.

[0007] Various methods have been proposed for pre-lithiation within batteries.

[0008] For example, one method of pre-lithiation at the cathode is to coat more cathode material to compensate for the amount of lithium consumed at the anode. However, due to the low capacity of the cathode material itself, the amount of additional material increases, and consequently, the energy density and capacity per unit weight of the final battery decrease by the same amount.

[0009] Accordingly, materials suitable for the pre-lithiation of batteries at the cathode must possess irreversible characteristics, such as allowing at least twice as much lithium to be released compared to conventional cathode materials during the first charge, while remaining non-reactive with lithium during subsequent discharge. Additives that satisfy these conditions are called sacrificial positive electrode materials.

[0010] Meanwhile, Li2NiO2 compounds have been used as cathode additives, acting as sacrificial cathode materials, for the pre-lithiation of anodes containing SiO. However, to secure the irreversible capacity for pre-lithiation, at least 3 wt% of Li2NiO2 compounds relative to the cathode material is required. When Li2NiO2 compounds, which have relatively lower stability, are added in excess, safety issues may arise, such as reduced thermal stability of the lithium secondary battery and increased gas generation.

[0011] When polylithium metal oxides such as Li6CoO4, Li5FeO4, and Li6MnO4 are used as cathode additives to increase irreversible capacity, the effect of pre-lithiation can be obtained with an additive amount of about one-third compared to Li2NiO2 compounds, and thermal stability can also be improved. However, the above polylithium metal oxides have a higher gas generation rate compared to Li2NiO2 compounds and exhibit side effects such as increased battery resistance due to the leaching of metal elements. The problem to be solved

[0013] The present invention is intended to provide a cathode additive that can improve the safety of a lithium secondary battery by having a stable crystalline phase while enabling an improvement in irreversible capacity.

[0014] The present invention is intended to provide a method for manufacturing the above-mentioned anode additive.

[0015] And, the present invention is intended to provide a lithium secondary battery comprising the above-mentioned anode additive. means of solving the problem

[0017] According to one embodiment of the invention,

[0018] A cathode additive for a lithium secondary battery is provided, comprising a compound represented by the following chemical formula 1:

[0019] [Chemical Formula 1]

[0020] a(Li2Ni 1-x Cu x O2)-b(Li y MO z )

[0021] In the above chemical formula 1,

[0022] M is Co, Mn, or Fe, and

[0023] a and b are Li2Ni contained in the compound of Formula 1 above. 1-x Cu x O2 crystalline phase and Li y MO z As molar ratios of the crystalline phases, 0.5 ≤ a ≤ 0.9 and 0.1 ≤ b ≤ 0.5, and

[0024] 0.1 ≤ x ≤ 0.4, 3 < y < 7, and 3 < z < 5.

[0026] According to another embodiment of the invention,

[0027] A step of heat-treating a precursor mixture comprising a lithium precursor, a nickel precursor, a copper precursor, and the precursor of M below under an inert gas atmosphere to form a compound represented by Chemical Formula 1.

[0028] A method for manufacturing a positive electrode additive for a lithium secondary battery, comprising:

[0030] According to another embodiment of the invention, a positive electrode for a lithium secondary battery comprising the positive electrode additive is provided.

[0032] According to another embodiment of the invention, a lithium secondary battery is provided, comprising a positive electrode for the lithium secondary battery; a negative electrode; a separator; and an electrolyte.

[0034] Hereinafter, a positive electrode additive for a lithium secondary battery according to embodiments of the invention, a method for manufacturing the same, and a lithium secondary battery including the same will be described in more detail.

[0036] Terms and words used in this specification and claims should not be interpreted as being limited to their ordinary or dictionary meanings, but should be interpreted in a meaning and concept consistent with the technical idea of ​​the invention, based on the principle that the inventor can appropriately define the concept of the terms to best describe his invention.

[0037] Unless otherwise defined in this specification, all technical and scientific terms have the same meaning as generally understood by those skilled in the art to which the invention pertains. The terms used in the description of the invention are merely for the purpose of effectively describing specific embodiments and are not intended to limit the invention.

[0038] The singular forms used in this specification include plural forms unless the phrases clearly indicate otherwise.

[0039] As used in this specification, the meaning of “includes” specifies certain characteristics, regions, integers, steps, actions, elements, and / or components, and does not exclude the existence or addition of other specific characteristics, regions, integers, steps, actions, elements, components, and / or groups.

[0040] The present invention is capable of various modifications and may take various forms, and specific embodiments are illustrated and described in detail below. However, this is not intended to limit the invention to the specific disclosed forms, and it should be understood that the invention includes all modifications, equivalents, and substitutions that fall within the spirit and scope of the invention.

[0041] In this specification, where the positional relationship between two parts is described, for example, using expressions such as 'on', 'on the upper part', 'on the lower part', 'next to', etc., one or more other parts may be located between the two parts unless expressions such as 'immediately' or 'directly' are used.

[0042] In this specification, when temporal sequences are described, for example, using expressions such as ‘after,’ ‘following,’ ‘next,’ or ‘before,’ cases that are not continuous may be included unless expressions such as ‘immediately’ or ‘directly’ are used.

[0043] In this specification, the term 'at least one' should be understood to include all combinations that can be presented from one or more related items.

[0046] According to one embodiment of the invention,

[0047] A cathode additive for a lithium secondary battery is provided, comprising a compound represented by the following chemical formula 1:

[0048] [Chemical Formula 1]

[0049] a(Li2Ni 1-x Cu x O2)-b(Li y MO z )

[0050] In the above chemical formula 1,

[0051] M is Co, Mn, or Fe, and

[0052] a and b are Li2Ni contained in the compound of Formula 1 above. 1-x Cu xO2 crystalline phase and Li y MO z As molar ratios of the crystalline phases, 0.5 ≤ a ≤ 0.9 and 0.1 ≤ b ≤ 0.5, and

[0053] 0.1 ≤ x ≤ 0.4, 3 < y < 7, and 3 < z < 5.

[0055] The compound of Chemical Formula 1 above is a composite formed by heat-treating a mixture containing a lithium precursor, a nickel precursor, and the precursor of M in the presence of a copper precursor according to the manufacturing method described below.

[0056] The compound of Chemical Formula 1 above is the Li2Ni 1-x Cu x O2 crystalline phase and the above Li y MO z It has a complex crystal phase in which crystal phases are mixed. Here, the term "forming the complex crystal phase" refers to the Li2Ni 1-x Cu x O2 crystalline phase and the above Li y MO z This may mean that crystalline phases exist in an aggregated single particle state. This refers to Li2Ni 1-x Cu x O2 compounds and Li y MO z The primary particles of the compound can be distinguished from a state in which they are simply mixed physically or mechanically.

[0058] According to one embodiment, in the above formula 1, M is an element capable of forming a crystalline phase of a polylithium metal oxide. Specifically, M may be Co, Mn, or Fe.

[0060] In the above Chemical Formula 1, a and b are Li2Ni contained in the compound of the above Chemical Formula 1. 1-x Cu x O2 crystalline phase and Li y MO zThe molar ratio of the crystalline phase (a+b=1) may be 0.5 ≤ a ≤ 0.9 and 0.1 ≤ b ≤ 0.5. That is, in the above chemical formula 1, a : b may be 1 : 1 to 9 : 1.

[0061] In order for the compound of Formula 1 above to exhibit an enhanced irreversible capacity, it is preferable that b is 0.1 or more, or 0.15 or more, or 0.2 or more; and that a is 0.9 or less, or 0.85 or less, or 0.8 or less. However, if b is excessively large, the amount of gas generated by the compound may increase. Therefore, it is preferable that b is 0.5 or less, or 0.4 or less, or 0.3 or less; and that a is 0.5 or more, or 0.6 or more, or 0.7 or more.

[0062] Preferably, the above a may be 0.5 to 0.9, or 0.6 to 0.9, or 0.6 to 0.85, or 0.7 to 0.85, or 0.7 to 0.8. And, the above b may be 0.1 to 0.5, or 0.15 to 0.5, or 0.15 to 0.4, or 0.2 to 0.4, or 0.2 to 0.3.

[0064] In the above chemical formula 1, x is the mole fraction of copper (Cu) substituting for a portion of nickel (Ni). Specifically, x may be 0.1 or more, or 0.15 or more, or 0.2 or more; and 0.4 or less, or 0.35 or less, or 0.3 or less.

[0065] In order to prevent the formation of a nickel oxide (NiO) secondary phase during the synthesis process of the compound of Formula 1, it is preferable that x be 0.1 or more, or 0.15 or more, or 0.2 or more. However, if copper (Cu) is included in excess in the compound of Formula 1, the charging capacity may be relatively reduced. Therefore, it is preferable that x be 0.4 or less, or 0.35 or less, or 0.3 or less.

[0066] Preferably, the above x may be 0.1 to 0.4, or 0.15 to 0.4, or 0.15 to 0.35, or 0.2 to 0.35, or 0.2 to 0.3.

[0068] In the above chemical formula 1, y may be greater than 3 and less than 7, or 3.5 to 6.5, or 4 to 6.5, or 4.5 to 6.5, or 5 to 6.5. Also, in the above chemical formula 1, z may be greater than 3 and less than 5, or 3.5 to 4.5.

[0070] By satisfying the above-mentioned numerical range, the compound of Formula 1 enables an improvement in irreversible capacity compared to previously known irreversible anode additives, while also enabling improved thermal stability and suppression of gas generation.

[0072] The compound of Chemical Formula 1 above is the Li2Ni 1-x Cu x O2 crystalline phase and the above Li y MO z It has a complex crystal phase in which crystal phases are mixed. Accordingly, when powder X-ray diffraction analysis is performed on the compound of Chemical Formula 1, characteristic peaks attributed to the complex crystal phase can be observed.

[0073] According to one embodiment, the compound of Formula 1 may have peaks appearing at 2θ of 19°±0.5°, 26°±0.5°, 37°±0.5°, and 43°±0.5° when analyzed by powder X-ray diffraction by Cu Kα X-ray (X-rα).

[0074] In the powder X-ray diffraction analysis above, the peaks appearing at 2θ of 19°±0.5° and 26°±0.5° are the Li2Ni 1-x Cu x These are characteristic peaks originating from the O2 crystal phase. Also, the peaks appearing at 2θ at 37°±0.5° and 43°±0.5° are characteristic peaks originating from the unreacted nickel precursor in the precursor mixture applied to prepare the compound of Formula 1 above. For reference, Li2Ni 1-x Cu x O2 compounds and Li y MO z When the primary particles of the compound are simply mixed physically or mechanically, the peaks appearing at 2θ of 37°±0.5° and 43°±0.5° are not observed.

[0075] And, the compound of Chemical Formula 1 above is Li when analyzed by X-ray diffraction of the powder. y MO z It has characteristic peaks originating from the crystalline phase. For example, when M is Fe, the compound of Formula 1 is Li y MO z It may have peaks appearing at 2θ of 21.5°±0.5° and 24°±0.5° originating from.

[0077] The compound of Chemical Formula 1 above may have the form of primary particles having a volume average particle size (D50) of 0.5 μm to 45 μm, or 1 μm to 25 μm, or 5 μm to 20 μm, or secondary particles formed by the aggregation of the primary particles. Within the above particle size range, the anode additive can be uniformly mixed with the anode active material to exhibit appropriate characteristics within the anode.

[0078] In order to have an appropriate particle size distribution and volume average particle size, the compound of Formula 1 can be synthesized, and then the compound particles can be passed through a standard sieve having a mesh size corresponding to the desired particle size distribution. The particle size distribution and volume average particle size (D50) of the compound can be measured and calculated using a well-known laser particle size analyzer, etc.

[0080] The compound of Chemical Formula 1 above has the characteristic of irreversibly releasing lithium during the charging and discharging of a lithium secondary battery. Therefore, the compound of Chemical Formula 1 above can be included in a positive electrode for a lithium secondary battery and can serve as a sacrificial positive electrode material for pre-lithiation.

[0083] According to another embodiment of the invention,

[0084] A step of heat-treating a precursor mixture comprising a lithium precursor, a nickel precursor, a copper precursor, and the precursor of M below under an inert gas atmosphere to form a compound represented by the following chemical formula 1.

[0085] A method for manufacturing a cathode additive for a lithium secondary battery, comprising:

[0086] [Chemical Formula 1]

[0087] a(Li2Ni 1-x Cu x O2)-b(Li y MO z )

[0088] In the above chemical formula 1,

[0089] M is Co, Mn, or Fe, and

[0090] a and b are Li2Ni contained in the compound of Formula 1 above. 1-x Cu x O2 and Li y MO zAs the molar ratios of , 0.5 ≤ a ≤ 0.9 and 0.1 ≤ b ≤ 0.5, and

[0091] 0.1 ≤ x ≤ 0.4, 3 < y < 7, and 3 < z < 5.

[0093] As previously explained, among the cathode additives known as sacrificial cathode materials, Li2NiO2 compounds require an excessive amount to secure irreversible capacity, causing safety issues in lithium secondary batteries. Additionally, polylithium metal oxides such as Li6CoO4, Li5FeO4, and Li6MnO4 have high gas generation rates and cause adverse effects due to the leaching of metal elements.

[0094] To improve the irreversible capacity of Li2NiO2 compounds, a method of adding the aforementioned polylithium metal oxide precursor during the synthesis of Li2NiO2 compounds can be considered. However, in this synthesis method, due to the mixing problem of nickel (Ni) and other transition metals, the Li2NiO2 phase is not formed and tends to precipitate as nickel oxide.

[0095] In addition, it has been proposed to use a mixture of Li2NiO2 compounds and Li2CuO2 compounds as an anode additive, but it is known that there is almost no improvement in irreversible capacity due to the addition of Li2CuO2 compounds.

[0097] However, according to the results of the inventors' research, by heat-treating a mixture comprising a lithium precursor, a nickel precursor, and the precursor of M in the presence of a copper precursor, the Li2Ni is produced without the precipitation of nickel oxide. 1-x Cu x Crystalline phase of O2 and the above Li y MO z A compound of the above chemical formula 1, which is a complex crystalline phase in which the crystalline phases are mixed, can be prepared.

[0099] According to one embodiment, a precursor mixture including a lithium precursor, a nickel precursor, a copper precursor, and the precursor of M is heat-treated under an inert gas atmosphere to form a compound represented by the chemical formula 1.

[0100] The above precursor mixture can be prepared by solid-state mixing of a lithium precursor, a nickel precursor, a copper precursor, and the precursor of M in a stoichiometric ratio according to Formula 1.

[0101] As the above precursors, compounds known in the technical field to which the present invention belongs to be usable as precursors of the corresponding element may be applied without special limitation.

[0102] Preferably, the lithium precursor may be a lithium oxide, a lithium hydroxide, or a lithium carbonate.

[0103] The nickel precursor may be one or more compounds selected from the group consisting of nickel oxide, nickel hydroxide, nickel sulfate, nickel nitrate, nickel acetate, nickel carbonate, nickel oxalate, nickel citrate, nickel halide, nickel phosphate, and hydroxides thereof.

[0104] The copper precursor may be one or more compounds selected from the group consisting of copper oxide, copper hydroxide, copper sulfate, copper nitrate, copper acetate, copper carbonate, copper oxalate, copper citrate, copper halide, copper phosphate, and hydroxides thereof.

[0105] And, the precursor of the above M may be one or more compounds selected from the group consisting of oxides, hydroxides, sulfates, nitrates, acetates, carbonates, oxalates, citrates, halides, phosphates, and hydroxides containing element M.

[0107] According to one embodiment, the heat treatment may be performed for 3 to 18 hours under an inert gas atmosphere and a temperature of 600 ℃ to 1000 ℃.

[0108] The above heat treatment can be performed under an inert gas atmosphere such as Ar, N2, Ne, and He.

[0109] In order to generate crystal seeds at an appropriate rate, it is preferable that the heat treatment be performed at a temperature of 600°C or higher or 700°C or higher. However, if the temperature of the heat treatment is excessively high, a sintering phenomenon may occur in which the grown particles clump together. Therefore, it is preferable that the heat treatment be performed at a temperature of 1000°C or lower or 900°C or lower. Specifically, the heat treatment may be performed at a temperature of 600°C to 1000°C, 700°C to 1000°C, or 700°C to 900°C.

[0110] The heat treatment may be performed for 3 to 18 hours at the heat treatment temperature. The heat treatment time may be adjusted by taking into account the time required for the precursors to react sufficiently and the time required for the crystal of the compound of Formula 1 to stabilize. Specifically, the heat treatment time may be 3 hours or more or 5 hours or more; and 18 hours or less or 15 hours or less. Preferably, the heat treatment time may be 3 to 18 hours, or 5 to 18 hours, or 5 to 15 hours.

[0112] If necessary, a step of grinding the compound of Formula 1 obtained in the above step may be performed.

[0113] If the difference in particle size between the cathode active material and the cathode additive in the cathode material increases, it becomes difficult to achieve uniform mixing of the cathode material and the internal stress of the electrode increases, which may make it difficult to achieve stable battery performance.

[0114] The particle size of the anode additive obtained through the above grinding can be determined to be similar to that of the anode active material. However, it is not desirable to apply energy during the grinding process to the extent that excessive fine powder is generated.

[0115] As a non-limiting example, the grinding may be performed by pre-grinding, which grinds the anode additive obtained in the form of lumps in the above step into chunks on a scale of several cm; coarse grinding, which grinds the chunks to 1 mm or less; and fine grinding using a pin mill, etc. Afterward, it may be classified using a standard sieve.

[0118] According to another embodiment of the invention, a positive electrode for a lithium secondary battery comprising the positive electrode additive is provided.

[0119] The positive electrode for the lithium secondary battery may include a positive electrode active material, a binder, a conductive material, and the positive electrode additive. Preferably, the positive electrode for the lithium secondary battery comprises a positive electrode material comprising a positive electrode active material, a conductive material, the positive electrode additive, and a binder; and a current collector supporting the positive electrode material.

[0120] According to one embodiment, the anode additive may be included in an amount greater than 0 weight% and less than or equal to 15 weight% relative to the total weight of the anode material.

[0121] In order to compensate for the irreversible lithium consumed in the formation of the SEI layer, it is preferable that the content of the lithium transition metal oxide be greater than 0 weight% relative to the total weight of the cathode material. However, if the cathode additive, which is a sacrificial cathode material, is included in excess, the content of the cathode active material exhibiting reversible charge / discharge capacity decreases, thereby reducing the capacity of the battery, and residual lithium within the battery may be plated onto the negative electrode, causing a short circuit in the battery or compromising safety. Therefore, it is preferable that the content of the cathode additive be 15 weight% or less relative to the total weight of the cathode material.

[0122] Specifically, the content of the anode additive may be greater than 0 wt%, or 0.5 wt% or more, or 1 wt% or more, or 2 wt% or more, or 3 wt% or more relative to the total weight of the anode material; and, 15 wt% or less, or 12 wt% or less, or 10 wt% or less. Preferably, the content of the anode additive may be 0.5 wt% to 15 wt%, or 1 wt% to 15 wt%, or 1 wt% to 12 wt%, or 2 wt% to 12 wt%, or 2 wt% to 10 wt%, or 3 wt% to 10 wt% relative to the total weight of the anode material.

[0124] As the above-mentioned positive electrode active material, any material capable of reversible insertion and extraction of lithium ions may be used without special limitations. For example, the above-mentioned positive electrode active material may be a complex oxide or phosphate containing lithium and metals such as cobalt, manganese, nickel, iron, or a combination thereof.

[0125] As a non-limiting example, the positive active material may be a compound represented by any one of the following chemical formulas.

[0126] Li a A 1-b R b D2(0.90≤a≤1.8, 0≤b≤0.5); Li a E 1-b R b O 2-c D c (0.90≤a≤1.8, 0≤b≤0.5, 0≤c≤0.05); LiE 2-b R b O 4-c D c (0≤b≤0.5, 0≤c≤0.05); Li a Ni 1-b-c Co b R c D d (0.90≤a≤1.8, 0≤b≤0.5, 0≤c≤0.05, 0 <d≤2); Li a Ni 1-b-c Cob R c O 2-d Z d (0.90≤a≤1.8, 0≤b≤0.5, 0≤c≤0.05, 0 <d<2); Li a Ni 1-b-c Co b R c O 2-d Z2(0.90≤a≤1.8, 0≤b≤0.5, 0≤c≤0.05, 0 <d<2); Li a Ni 1-b-c Mr b R c D d (0.90≤a≤1.8, 0≤b≤0.5, 0≤c≤0.05, 0 <d≤2); Li a Ni 1-b-c Mr b R c O 2-d Z d (0.90≤a≤1.8, 0≤b≤0.5, 0≤c≤0.05, 0 <d<2); Li a Ni 1-b-c Mr b R c O 2-d Z2(0.90≤a≤1.8, 0≤b≤0.5, 0≤c≤0.05, 0 <d<2); Li a Ni b HAVE BEEN c G d O2(0.90≤a≤1.8, 0≤b≤0.9, 0≤c≤0.5, 0.001≤d≤0.1.); Li a Ni b Co c Mr d G e O2(0.90≤a≤1.8, 0≤b≤0.9, 0≤c≤0.5, 0≤d≤0.5, 0.001≤e≤0.1); Li a NiG b O2(0.90≤a≤1.8, 0.001≤b≤0.1); Li a CoG b O2(0.90≤a≤1.8, 0.001≤b≤0.1); Li a MnG b O2(0.90≤a≤1.8, 0.001≤b≤0.1); Li a Mn2Gb O4(0.90≤a≤1.8, 0.001≤b≤0.1); QO2; QS2; LiQS2; V2O5; LiV2O5; LiTO2; LiNiVO4; Li (3-f) J2(PO4)3(0≤f≤2); Li (3-f) Fe2(PO4)3(0≤f≤2); and LiFePO4.

[0127] In the above chemical formula, A is Ni, Co, Mn or a combination thereof; R is Al, Ni, Co, Mn, Cr, Fe, Mg, Sr, V, a rare earth element or a combination thereof; D is O, F, S, P or a combination thereof; E is Co, Mn or a combination thereof; Z is F, S, P or a combination thereof; G is Al, Cr, Mn, Fe, Mg, La, Ce, Sr, V or a combination thereof; Q is Ti, Mo, Mn or a combination thereof; T is Cr, V, Fe, Sc, Y or a combination thereof; and J is V, Cr, Mn, Co, Ni, Cu or a combination thereof.

[0128] Of course, a coating layer on the surface of the above-mentioned positive active material may be used, or a mixture of the above-mentioned positive active material and the positive active material having a coating layer may be used. As coating elements included in the above-mentioned coating layer, Mg, Al, Co, K, Na, Ca, Si, Ti, V, Sn, Ge, Ga, B, As, Zr, or a mixture thereof may be used.

[0129] According to one embodiment, the positive active material may be included in an amount of 80% to 95% by weight relative to the total weight of the positive material.

[0130] Specifically, the content of the positive electrode active material may be 80 weight% or more, or 82 weight% or more, or 85 weight% or more relative to the total weight of the positive electrode material; and, 95 weight% or less, or 93 weight% or less, or 90 weight% or less.

[0131] Preferably, the content of the positive active material may be 82% to 95% by weight, or 82% to 93% by weight, or 85% to 93% by weight, or 85% to 90% by weight, relative to the total weight of the positive material.

[0133] The above conductive material is used to impart conductivity to the electrode.

[0134] The above conductive material may be used without special limitations as long as it possesses electronic conductivity without causing chemical changes in the battery. As a non-limiting example, the above conductive material may be carbon-based materials such as carbon black, acetylene black, Ketjen black, channel black, furnace black, lamp black, thermal black, carbon fiber; graphite such as natural graphite or artificial graphite; metal powder or metal fiber such as copper, nickel, aluminum, or silver; conductive whiskey such as zinc oxide or potassium titanate; conductive metal oxide such as titanium oxide; or conductive polymers such as polyphenylene derivatives. As the above conductive material, one or more of the examples described above may be used.

[0135] The content of the conductive material can be adjusted within a range that does not cause a reduction in battery capacity while exhibiting an appropriate level of conductivity. Preferably, the content of the conductive material may be 1% to 10% by weight or 1% to 5% by weight relative to the total weight of the cathode material.

[0137] The above binder is used to properly attach the above anode material to the above current collector.

[0138] As a non-limiting example, the binder may be polyvinyl alcohol, carboxymethylcellulose, hydroxypropylcellulose, diacetylcellulose, polyvinyl chloride, carboxylated polyvinyl chloride, polyvinyl fluoride, a polymer containing ethylene oxide, polyvinylpyrrolidone, polyurethane, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene, polypropylene, styrene-butadiene rubber, acrylated styrene-butadiene rubber, epoxy resin, nylon, etc. As the binder, one or more of the examples described above may be used.

[0139] The content of the binder can be adjusted within a range that does not cause a reduction in battery capacity while exhibiting an appropriate level of adhesion. Preferably, the content of the binder may be 1% to 10% by weight or 1% to 5% by weight relative to the total weight of the cathode material.

[0141] As the above current collector, any material known to be applicable to the positive electrode of a lithium secondary battery in the technical field to which the present invention belongs may be used without special limitations.

[0142] As a non-limiting example, the above current collector may be stainless steel; aluminum; nickel; titanium; calcined carbon; or aluminum or stainless steel surface treated with carbon, nickel, titanium, silver, etc.

[0143] Preferably, the current collector may have a thickness of 3 μm to 500 μm. In order to increase the adhesion of the anode material, the current collector may have fine irregularities formed on its surface. The current collector may have various forms, such as a film, sheet, foil, net, porous body, foam, nonwoven fabric, etc.

[0145] The positive electrode for the lithium secondary battery can be formed by applying a positive electrode material comprising the positive electrode active material, the conductive material, the positive electrode additive, and a binder onto the current collector.

[0148] According to another embodiment of the invention, a lithium secondary battery is provided, comprising a positive electrode for the lithium secondary battery; a negative electrode; a separator; and an electrolyte.

[0149] The above lithium secondary battery comprises a cathode including the above cathode additive. Accordingly, the above lithium secondary battery can exhibit improved irreversible capacity and improved safety. In addition, the above lithium secondary battery can exhibit high discharge capacity, excellent output characteristics, and capacity retention rate.

[0150] The above lithium secondary battery can be used as an energy source with enhanced performance and safety in the field of portable electronic devices such as mobile phones, laptop computers, tablet computers, mobile batteries, and digital cameras; and in the field of means of transportation such as electric vehicles, electric motorcycles, and personal mobility devices.

[0152] The above lithium secondary battery may include an electrode assembly wound with a separator interposed between a positive electrode and a negative electrode, and a case in which the electrode assembly is housed. Additionally, the positive electrode, the negative electrode, and the separator may be impregnated with an electrolyte.

[0153] The above lithium secondary battery can have various shapes, such as prismatic, cylindrical, and pouch types.

[0154] The details regarding the above anode are replaced by the contents described in the item regarding the anode for the above lithium secondary battery.

[0156] The above cathode may include a cathode material comprising a cathode active material, a conductive material, and a binder; and a current collector supporting the cathode material.

[0157] The above-mentioned negative electrode active material may include a material capable of reversibly intercalating and deintercalating lithium ions, lithium metal, an alloy of lithium metal, a material capable of doping and dedoping lithium, and a transition metal oxide.

[0158] Examples of materials capable of reversibly intercalating and deintercalating the above lithium ions include carbonaceous materials such as crystalline carbon, amorphous carbon, or mixtures thereof. Specifically, the carbonaceous materials may be natural graphite, artificial graphite, Kish graphite, pyrolytic carbon, mesophase pitches, mesophase pitch-based carbon fibers, meso-carbon microbeads, petroleum or coal tar pitch-derived cokes, soft carbon, and hard carbon.

[0159] The above lithium metal alloy may be an alloy of lithium and a metal selected from the group consisting of Na, K, Rb, Cs, Fr, Be, Mg, Ca, Sr, Si, Sb, Pb, In, Zn, Ba, Ra, Ge, Al, Sn, Bi, Ga, and Cd.

[0160] The materials capable of doping and dedoping the above lithium are Si, Si-C complexes, SiOx (0 <x<2), Si-Q 합금(상기 Q는 알칼리 금속, 알칼리 토금속, 13족 원소, 14족 원소, 15족 원소, 16족 원소, 전이 금속, 희토류 원소, 및 이들의 조합으로 이루어진 군에서 선택되는 원소이다; 단, Si는 제외한다), Sn, SnO2, Sn-R 합금(상기 R은 알칼리 금속, 알칼리 토금속, 13족 원소, 14족 원소, 15족 원소, 16족 원소, 전이 금속, 희토류 원소, 및 이들의 조합으로 이루어진 군에서 선택되는 원소이다; 단, Sn은 제외한다.) 등일 수 있다. 그리고, 상기 리튬에 도프 및 탈도프 가능한 물질로는 상기 예들 중 적어도 하나와 SiO2를 혼합하여 사용할 수 있다. 상기 Q 및 R은 Mg, Ca, Sr, Ba, Ra, Sc, Y, Ti, Zr, Hf, Rf, V, Nb, Ta, Db, Cr, Mo, W, Sg, Tc, Re, Bh, Fe, Pb, Ru, Os, Hs, Rh, Ir, Pd, Pt, Cu, Ag, Au, Zn, Cd, B, Al, Ga, Sn, In, Tl, Ge, P, As, Sb, Bi, S, Se, Te, Po 등일 수 있다.

[0161] And, the above transition metal oxide may be vanadium oxide, lithium vanadium oxide, lithium titanium oxide, etc.

[0162] Preferably, the cathode may include one or more cathode active materials selected from the group consisting of carbonaceous materials and silicon compounds.

[0163] That is, according to another embodiment of the invention, a lithium secondary battery is provided comprising: a positive electrode for the lithium secondary battery; a negative electrode comprising one or more negative active materials selected from the group consisting of carbonaceous materials and silicon compounds; a separator; and an electrolyte.

[0164] Here, the carbonaceous material is one or more materials selected from the group consisting of natural graphite, artificial graphite, Kish graphite, pyrolytic carbon, mesophase pitch, mesophase pitch-based carbon fibers, carbon microspheres, petroleum or coal-based coke, softened carbon, and hardened carbon, as previously exemplified. And, the silicon compound is a compound containing Si as previously exemplified, namely Si, Si-C complexes, SiOx (0 <x<2), 상기 Si-Q 합금, 이들의 혼합물, 또는 이들 중 적어도 하나와 SiO2의 혼합물일 수 있다.

[0165] According to one embodiment, the negative electrode active material may be included in an amount of 85% to 98% by weight relative to the total weight of the negative electrode material.

[0166] Specifically, the content of the cathode active material may be 85 weight% or more, or 87 weight% or more, or 90 weight% or more relative to the total weight of the cathode material; and, 98 weight% or less, or 97 weight% or less, or 95 weight% or less.

[0167] Preferably, the content of the cathode active material may be 85% to 97% by weight, or 87% to 97% by weight, or 87% to 95% by weight, or 90% to 95% by weight, relative to the total weight of the cathode material.

[0168] The conductive material, the binder, and the current collector included in the above-mentioned cathode material are described in the section on the positive electrode for the lithium secondary battery.

[0169] The above-mentioned separator separates the positive and negative electrodes and provides a pathway for the movement of lithium ions. Any separator known in the art to which the present invention belongs to be applicable to a separator of a lithium secondary battery may be used without any particular limitations. It is preferable that the separator has low resistance to the movement of electrolyte ions and excellent wettability to the electrolyte.

[0170] Specifically, the separator may be a porous polymer film made of a polyolefin-based polymer such as polyethylene, polypropylene, ethylene-butene copolymer, ethylene-hexene copolymer, ethylene-methacrylate copolymer, etc. The separator may be a multilayer film in which the porous polymer film is laminated in two or more layers. The separator may be a nonwoven fabric including glass fibers, polyethylene terephthalate fibers, etc. Additionally, the separator may be coated with a ceramic component or a polymer material to ensure heat resistance or mechanical strength.

[0172] Meanwhile, the above electrolyte may be used without special limitations as long as it is known to be applicable to lithium secondary batteries in the technical field to which the present invention belongs. For example, the above electrolyte may be an organic liquid electrolyte, an inorganic liquid electrolyte, a solid polymer electrolyte, a gel-type polymer electrolyte, a solid inorganic electrolyte, a molten inorganic electrolyte, etc.

[0173] Specifically, the electrolyte may include a non-aqueous organic solvent and a lithium salt.

[0174] The above-mentioned non-aqueous organic solvent can be used without special restrictions as long as it can serve as a medium through which ions involved in the electrochemical reaction of the battery can move.

[0175] Specifically, the non-aqueous organic solvent is an ester-based solvent such as methyl acetate, ethyl acetate, γ-butyrolactone, and ε-caprolactone; an ether-based solvent such as dibutyl ether and tetrahydrofuran; a ketone-based solvent such as cyclohexanone; an aromatic hydrocarbon-based solvent such as benzene and fluorobenzene; and a carbonate-based solvent such as dimethyl carbonate (DMC), diethyl carbonate (DEC), methyl ethyl carbonate (MEC), ethyl methyl carbonate (EMC), ethylene carbonate (EC), and propylene carbonate (PC). Alcohol-based solvents such as ethyl alcohol and isopropyl alcohol; nitriles such as R-CN (where R is a straight-chain, branched, or cyclic hydrocarbon group having C2 to C20 and may include a double bond, directional ring, or ether bond); amides such as dimethylformamide; dioxolanes such as 1,3-dioxolane; and sulfolanes, etc.

[0176] Among the above examples, a carbonate-based solvent may preferably be used as the above-mentioned non-aqueous organic solvent.

[0177] In particular, considering the charge / discharge performance of the battery and compatibility with the sacrificial cathode material, a mixture of a cyclic carbonate having high ionic conductivity and high dielectric constant (e.g., ethylene carbonate, propylene carbonate) and a linear carbonate having low viscosity (e.g., ethyl methyl carbonate, dimethyl carbonate, diethyl carbonate) may preferably be used as the non-aqueous organic solvent. In this case, using a mixture of the cyclic carbonate and the linear carbonate in a volume ratio of 1:1 to 1:9 may be advantageous for exhibiting the aforementioned performance.

[0178] In addition, the above-mentioned non-aqueous organic solvent may preferably be a mixture of ethylene carbonate (EC) and ethyl methyl carbonate (EMC) in a volume ratio of 1:2 to 1:10; or a mixture of ethylene carbonate (EC), ethyl methyl carbonate (EMC) and dimethyl carbonate (DMC) in a volume ratio of 1 to 3:1 to 9:1.

[0179] The lithium salt included in the above electrolyte is dissolved in the above-mentioned non-aqueous organic solvent and acts as a source of lithium ions within the battery, enabling the operation of a basic lithium secondary battery and facilitating the movement of lithium ions between the positive and negative electrodes.

[0180] Specifically, the lithium salt may be LiPF6, LiClO4, LiAsF6, LiBF4, LiSbF6, LiAlO4, LiAlCl4, LiCF3SO3, LiC4F9SO3, LiN(C2F5SO3)2, LiN(C2F5SO2)2, LiN(CF3SO2)2, LiN(SO2F)2 (LiFSI, lithium bis(fluorosulfonyl)imide), LiCl, LiI, and LiB(C2O4)2, etc. Preferably, the lithium salt may be LiPF6, LiFSI, and mixtures thereof.

[0181] The lithium salt may be included in the electrolyte at a concentration of 0.1 M to 2.0 M. The lithium salt included in the above concentration range enables excellent electrolyte performance by imparting appropriate conductivity and viscosity to the electrolyte.

[0182] Optionally, the electrolyte may include additives intended for improving the lifespan characteristics of the battery, suppressing the reduction of battery capacity, and improving the discharge capacity of the battery.

[0183] For example, the above additive may be a haloalkylene carbonate compound such as difluoroethylene carbonate, pyridine, triethylphosphite, triethanolamine, cyclic ether, ethylene diamine, n-glyme, triamide hexaphosphate, nitrobenzene derivative, sulfur, quinone imine dye, N-substituted oxazolidinone, N,N-substituted imidazolidine, ethylene glycol dialkyl ether, ammonium salt, pyrrole, 2-methoxyethanol, aluminum trichloride, etc. The above additive may be included in an amount of 0.1% to 5% by weight based on the total weight of the electrolyte. Effects of the invention

[0185] According to the present invention, a cathode additive is provided that can improve the safety of a lithium secondary battery by having a stable crystalline phase while enabling an improvement in irreversible capacity. Brief explanation of the drawing

[0187] Figures 1 to 4 are X-ray diffraction (XRD) analysis results for anode additives prepared in the embodiments and comparative examples of the invention. Specific details for implementing the invention

[0188] The operation and effects of the invention will be explained in more detail through the specific embodiments described below. However, these are presented merely as examples to aid in understanding the invention. The following embodiments are not intended to limit the scope of the invention in any way, and it will be obvious to those skilled in the art that various changes and modifications are possible within the scope and technical spirit of the invention.

[0190] Example 1

[0191] (1) Preparation of anode additives

[0192] 0.8 (Li2Ni) by the following method 0.75 Cu 0.25 O2)-0.2(Li5FeO4) compound was synthesized.

[0193] A total of 50 g of precursor mixture was prepared by mixing Li2O (Ganfeng Lithium), NiO (Sigma-Aldrich), CuO (Sigma-Aldrich), and Fe2O3 (Sigma-Aldrich) in the above equivalent ratios. The precursor mixture was placed in a mixer (Tefal BL142-AKR) and mixed for at least 5 minutes. The precursor mixture was placed in an alumina crucible and the lid was closed. The crucible was placed in a gas pressure sintering furnace and heat-treated for 12 hours under an N2 gas atmosphere and at 700 °C, after which it was cooled. The resulting compound particles were placed in a jaw crusher (Retsch BB50) and coarsely ground to a gap of 2 mm, and then ground at 18,000 rpm in a pin mill (Retsch ZM200). The crushed compound particles were classified into particles with a diameter of 38 μm or less using a sieve shaker.

[0194] (2) Manufacturing of lithium secondary batteries

[0195] The above 0.8 (Li2Ni 0.75 Cu0.25 An anode material slurry was prepared by mixing an O2)-0.2(Li5FeO4) compound, carbon black as a conductive material, and polyvinylidene fluoride (PVdF) as a binder in an organic solvent (N-methyl-2-pyrrolidone) in a weight ratio of 95:3:2. The anode material slurry was applied to one surface of a current collector, which is an aluminum foil with a thickness of 15 μm, and an anode was manufactured by rolling and drying (stamping size Φ14 mm).

[0196] A coin-shaped half-cell was manufactured by preparing the above anode, cathode, separator, and electrolyte. At this time, a Li-metal with a thickness of 300 μm (stamped size Φ15 mm) was used as the cathode. As the electrolyte, 1.0 M LiPF6 and 2 wt% vinylene carbonate (VC) were dissolved in a non-aqueous organic solvent mixed with ethylene carbonate (EC), dimethyl carbonate (DMC), and diethyl carbonate (DEC) in a volume ratio of 1:2:1. And, as the separator, a PE resin separator (manufactured by W-scope, WL20C, 20 μm) was used.

[0198] Example 2

[0199] (1) Preparation of anode additives

[0200] Except for changing the equivalent ratio of the precursors, 0.7 (Li2Ni) was prepared in the same manner as in Example 1 above. 0.75 Cu 0.25 O2)-0.3(Li5FeO4) compound was synthesized.

[0201] (2) Manufacturing of lithium secondary batteries

[0202] As an anode additive, the above 0.7 (Li2Ni 0.75 Cu 0.25 A lithium secondary battery was manufactured in the same manner as in Example 1, except that the O2)-0.3(Li5FeO4) compound was used.

[0204] Comparative Example 1

[0205] (1) Preparation of anode additives

[0206] A total of 50 g of precursor mixture was prepared by mixing Li2O (Ganfeng Lithium), NiO (Sigma-Aldrich), and Fe2O3 (Sigma-Aldrich) such that the molar ratio of Li:Fe:Ni was 2.6:0.2:0.8. A cathode additive was prepared in the same manner as in Example 1, except that the above precursor mixture was used. According to the XRD analysis results below, the cathode additive according to Comparative Example 1 is confirmed to be a mixture of Li5FeO4 and NiO.

[0207] (2) Manufacturing of lithium secondary batteries

[0208] A lithium secondary battery was manufactured in the same manner as in Example 1, except that the above-mentioned anode additive was used.

[0210] Comparative Example 2

[0211] (1) Preparation of anode additives

[0212] A total of 50 g of precursor mixture was prepared by mixing Li2O (Ganfeng Lithium), NiO (Sigma-Aldrich), and CoO (Sigma-Aldrich) such that the molar ratio of Li:Co:Ni was 3.2:0.3:0.7. An anode additive was prepared in the same manner as in Example 1, except that the above precursor mixture was used. According to the XRD analysis results below, the anode additive according to Comparative Example 2 is confirmed to be a mixture of Li2NiO2 and Li6CoO4.

[0213] (2) Manufacturing of lithium secondary batteries

[0214] A lithium secondary battery was manufactured in the same manner as in Example 1, except that the above-mentioned anode additive was used.

[0216] Comparative Example 3

[0217] (1) Preparation of anode additives

[0218] A total of 50 g of precursor mixture was prepared by mixing Li2O (Ganfeng Lithium), NiO (Sigma-Aldrich), and MnO2 (Sigma-Aldrich) such that the molar ratio of Li:Mn:Ni was 2.8:0.2:0.8. The anode additive was prepared in the same manner as in Example 1, except that the above precursor mixture was used. According to the XRD analysis results below, the anode additive according to Comparative Example 3 is confirmed to be a mixture of Li2NiO2 and NiO.

[0219] (2) Manufacturing of lithium secondary batteries

[0220] A lithium secondary battery was manufactured in the same manner as in Example 1, except that the above-mentioned anode additive was used.

[0222] Comparative Example 4

[0223] (1) Preparation of anode additives

[0224] Li2O (Ganfeng Lithium), NiO (Sigma-Aldrich), and CuO (Sigma-Aldrich) were mixed such that the molar ratio of Li:Ni:Cu was 2:0.75:0.25. The mixture was prepared into pellet form using a press and calcined at 750 °C under an Ar atmosphere to produce Li2Ni 0.75 Cu 0.25 O2 particles were obtained. The Li2Ni was obtained in the same manner as in Example 1 above. 0.75 Cu 0.25 O2 particles were crushed and classified.

[0225] Li2O (Ganfeng Lithium) and Fe2O3 (Sigma-Aldrich) were mixed such that the molar ratio of Li to Fe was 5:1. The mixture was prepared into pellets using a press and calcined at 750 °C under an Ar atmosphere to obtain Li5FeO4 particles. The Li5FeO4 particles were ground and classified in the same manner as in Example 1.

[0226] The above Li2Ni in the mixer (Tefal BL142-AKR) 0.75 Cu 0.25 An anode additive was prepared by adding O2 particles and the above Li5FeO4 particles in a weight ratio of 8:2 and mixing for at least 5 minutes.

[0227] (2) Manufacturing of lithium secondary batteries

[0228] A lithium secondary battery was manufactured in the same manner as in Example 1, except that the above-mentioned anode additive was used.

[0230] Test example

[0231] (1) X-ray diffraction analysis

[0232] Powder X-ray diffraction analysis was performed on the anode additives prepared in the above examples and comparative examples using an XRD analysis instrument (Bruker D4 Endeavor, Cu Kα X-ray (X-rα)). The results are shown in Fig. 1 (Example 1), Fig. 2 (Comparative Example 1), Fig. 3 (Comparative Example 2), and Fig. 4 (Comparative Example 3).

[0233] Referring to FIG. 1, 0.8 (Li2Ni of Example 1) 0.75 Cu 0.25 In O2)-0.2(Li5FeO4) compounds, Li2Ni 0.75 Cu 0.25Peaks at 2θ at 19°±0.5° and 26°±0.5° originating from the O2 crystal phase, peaks at 2θ at 21.5°±0.5° and 24°±0.5° originating from the Li5FeO4 crystal phase, and peaks at 2θ at 37°±0.5° and 43°±0.5° originating from the unreacted nickel precursor (NiO) were observed.

[0234] Referring to Fig. 2, in Comparative Example 1, the characteristic peaks due to the Li2NiO2 crystal phase were hardly observed, the characteristic peaks originating from the Li2NiO2-Li5FeO4 composite crystal phase were not observed, and the characteristic peaks originating from NiO appeared strongly.

[0235] Referring to Fig. 3, in Comparative Example 2 above, a characteristic peak originating from the composite crystal phase of Li2NiO2 crystal phase and Li6CoO4 crystal phase was weakly observed, but it was confirmed that a large amount of unreacted Li2O and NiO remained.

[0236] Referring to Fig. 4, in Comparative Example 3, a characteristic peak due to the Li2NiO2 crystal phase was observed weakly, and no characteristic peak due to the Li2NiO2-Li6MnO4 composite crystal phase was observed, and it was confirmed that a large amount of Li2O and NiO remained.

[0238] (2) Charge / Discharge Capacity and Gas Generation Amount

[0239] The lithium secondary batteries prepared in Example 1, Example 2, and Comparative Example 4 were charged to 4.25 V under a constant current of 60 mA / g and a constant voltage of 30 mA / g at 45 ℃, and discharged to 2.5 V under a constant current of 10 mA / g to conduct charge-discharge experiments. The primary charge capacity and primary discharge capacity were calculated through the charge-discharge experiments.

[0240] In addition, the amount of gas generated during the charge-discharge experiment was measured using a hydrometer (MATSUHAKU, TWD-150DM). The difference between the original weight of the lithium secondary battery and its weight in water was measured, the change in volume within the battery was calculated, and the amount of gas generated per unit weight was calculated by dividing the change in volume by the weight of the cathode additive.

[0242] Primary charge capacity (mAh / g) Primary discharge capacity (mAh / g) Irreversible capacity (mAh / g) Formation gas generation amount (mL / g) Example 1 462 111 350 0.275 Example 2 489 99 390 - Comparative Example 4 463 115 348 0.325

[0243] Referring to the results of the above test example, in the above embodiment, Li2Ni 0.75 Cu 0.25 A compound of a composite crystalline phase including an O2 crystalline phase and a Li5FeO4 crystalline phase was obtained, and it was confirmed that a lithium secondary battery containing said compound can suppress gas generation while exhibiting an irreversible capacity equivalent to or greater than that of Comparative Example 4.

[0244] Although the present invention has been described above by limited embodiments, the present invention is not limited thereto, and it is obvious that various modifications and variations are possible within the scope of the technical spirit of the present invention and the equivalent scope of the claims described below by those skilled in the art to which the present invention belongs.

Claims

Claim 1 A cathode additive for a lithium secondary battery comprising a compound represented by the following chemical formula 1: [Chemical Formula 1]a(Li2Ni 1-x Cu x O2)-b(Li y MO z In the above Chemical Formula 1, M is Co, Mn, or Fe, and a and b are Li2Ni contained in the compound of the above Chemical Formula 1. 1-x Cu x O2 crystalline phase and Li y MO z The molar ratios of the crystal phases are 0.5 ≤ a ≤ 0.9 and 0.1 ≤ b ≤ 0.5, 0.1 ≤ x ≤ 0.4, 3 < y < 7, and 3 < z < 5. Claim 2 In claim 1, the compound of formula 1 is the Li2Ni 1-x Cu x O2 crystalline phase and the above Li y MO z A cathode additive for a lithium secondary battery having a complex crystalline phase in which crystalline phases are mixed. Claim 3 A cathode additive for a lithium secondary battery according to claim 1, wherein the compound of Formula 1 has peaks appearing at 2θ of 19°±0.5°, 26°±0.5°, 37°±0.5°, and 43°±0.5° when analyzed by powder X-ray diffraction by Cu Kα X-ray (X-rα). Claim 4 A method for manufacturing a cathode additive for a lithium secondary battery according to claim 1, comprising the step of heat-treating a precursor mixture including a lithium precursor, a nickel precursor, a copper precursor, and a precursor of the following M under an inert gas atmosphere to form a compound represented by the following chemical formula 1: [Chemical Formula 1]a(Li2Ni 1-x Cu x O2)-b(Li y MO z In the above Chemical Formula 1, M is Co, Mn, or Fe, and a and b are Li2Ni contained in the compound of the above Chemical Formula 1. 1-x Cu x O2 and Li y MO z As mole ratios, 0.5 ≤ a ≤ 0.9 and 0.1 ≤ b ≤ 0.5, 0.1 ≤ x ≤ 0.4, 3 < y < 7, and 3 < z < 5. Claim 5 A method for manufacturing a cathode additive for a lithium secondary battery, wherein, in claim 4, the heat treatment is performed for 3 to 18 hours under an inert gas atmosphere and a temperature of 600 ℃ to 1000 ℃. Claim 6 A method for manufacturing a positive electrode additive for a lithium secondary battery, wherein, in claim 4, the lithium precursor is a lithium oxide, a lithium hydroxide, or a lithium carbonate. Claim 7 A method for manufacturing a cathode additive for a lithium secondary battery according to claim 4, wherein the nickel precursor is one or more compounds selected from the group consisting of nickel oxide, nickel hydroxide, nickel sulfate, nickel nitrate, nickel acetate, nickel carbonate, nickel oxalate, nickel citrate, nickel halide, nickel phosphate, and hydroxides thereof. Claim 8 A method for manufacturing a cathode additive for a lithium secondary battery according to claim 4, wherein the copper precursor is one or more compounds selected from the group consisting of copper oxide, copper hydroxide, copper sulfate, copper nitrate, copper acetate, copper carbonate, copper oxalate, copper citrate, copper halide, copper phosphate, and hydroxides thereof. Claim 9 A method for manufacturing a positive electrode additive for a lithium secondary battery, wherein, in claim 4, the precursor of M is one or more compounds selected from the group consisting of oxides, hydroxides, sulfates, nitrates, acetates, carbonates, oxalates, citrates, halides, phosphates, and hydroxides thereof, comprising M. Claim 10 A cathode for a lithium secondary battery comprising a cathode additive according to claim 1. Claim 11 A lithium secondary battery comprising a positive electrode; a negative electrode; a separator; and an electrolyte according to claim 10. Claim 12 A lithium secondary battery according to claim 11, wherein the cathode comprises one or more cathode active materials selected from the group consisting of carbonaceous materials and silicon compounds.

Citation Information

Patent Citations

  • Method for preparing positive electrode additives of lithium secondary battery

    KR1020190059242A

  • Additives for cathode, manufacturing method of the same, cathode including the same, and lithium recharegable battery including the same

    KR1020190063408A

  • Additives for cathode, manufacturing method of the same, cathode including the same, and lithium recharegable battery including the same

    KR1020190064424A

  • Additives for cathode, manufacturing method of the same, cathode including the same, lithium recharegable battery including the same

    KR1020200136240A

  • Irreversible additive, positive electrode material incluing the same, lithium secondary battery incluing the positive electrode material

    KR1020210056932A